Talent Management in The Era Of Big Data [In Arabic] - Boufroukh, Souad; Bouteghrine, Zahia (Finance and Business Economies Review, 2022)
This paper aims to study the importance of adopting big data in talent management, its applications, its barriers and challenges, we have presented the theoretical concepts related to talent management, big data and identifying the change that this type of data has brought on. Then we presented big data and its various applications in talent management such as recruitment, training, evaluation, determining paid performance and managing career paths, highlighting the most important values for adopting big data in human resources, including talent management in particular. In the last part, we reviewed the five groups of barriers to the adoption of big data (technological, economic, organizational, human and external environment)..